Nurse Role of Smoking Cessation for Thai Muslim Youths - ทองเนื่อง, พัชราวดี; แขกพงศ์, เจ๊ะเหล๊าะ (Princess of Naradhiwas University Journal, 2018)
Smoking is an extremely bad and unhealthy behavior that has to be prevented, especially towards young people. When they were very young, there was an upward trend for smoking. When they grew up, they became an addicted regular smoker. The majority of Thai Muslims live in the three southern border provinces of Thailand. The main reasons for their smoking behavior might be from social or environment context. In this paper it seems that the young Thai Muslims who are tobacco smokers do not carry out their duties properly, which leads to social problems such as substance abuse. For Muslim young smokers, most of them were not supported to quit smoking because they were not seriously ill until they were hospitalized. They had no chance to meet a nurse or health personnel. Therefore, nurses need to be aware for helping Muslim young smokers to quit smoking in their community and family, following the Islam’s principle and the 5’As of the Agency for Health Care Research and Quality (AHRQ) which consists of ask, advice, assess, assist, and arrange.